Intercultural Balinese Painting from the Classic to the Modern - I Wayan Setem (Mudra Jurnal Seni Budaya, 2010)
This article examines the representation mode painting like a change parallel to the profound transformation of the technical or theoretical knowledge, and also parallel to changes in the Balinese society values due to the physical evolution and the evolution of the system of values. In fact, within one century of painting it has been like moving from the classical, traditional, standard, homogeneous, local, and collectively turned into a painting that has been varied, heterogeneous, individual, and internationally with a modern twist. These waves of change occurred in the span of time through several stages, and most striking result from cash capitalistic economy and culture, especially tourism. In pre-colonial time the painting is a narrative religious functions until the time of breath commercialism modernist touches to always make innovations or changes. From the sacred space of temples and palaces to moving objects souvenirs, hotel interiors, fash- ion and even interior and exterior car. Developments of painting through innovation should not be inter- preted as a discontinuity (rapture) or discontinuity of the local context, but on the contrary, to appreciate again the classical values (pastiche), not by road of preserving it rigidly, but the process of reinterpretation and re-contextualization.